EXPERIENCES FROM IYS 2020, PUBLIC ENGAGEMENT AND AWARENESS ACTIVITIES IN TURKEY - Şaher, K.; Sezgin, H.; Dümen, A.Ş.; Nas, S.; Kulak, S.; Özçetin, Z. (European Acoustics Association, EAA, 2023)
The year 2020, which has been designated as the International Year of Sound with the intention of celebrating and promoting the importance of sound for science and society was ironically started as a silent and isolated year with the global COVID-19 pandemic. However, these unprecedented times and activities around the world, which explored the interaction between sound, technology and the society, presented sound experiences for humanity and the ecosystem that they have never had the opportunity to experience before. This study reports on the activities of Turkish Acoustical Society during these times and aims to draw attention to the benefits, challenges, and opportunities of the instruments for widening participation and spreading knowledge relating to sound. The main activities were public opinion survey on noise annoyance in dwellings before and during the pandemic, Turkish Glossary of Acoustic Terms, IYS Drawing and Composition Competition in Turkish schools and various seminars, interviews, podcast on social media channels. Our experience and findings suggest that designing and implementing activities that actively includes researchers, teachers, students and ordinary people may help increase public engagement behaviorally, emotionally, and cognitively, there by positively affecting awareness in sound related subjects. © 2023 First author et al. This is an open-access article distributed under the terms of the Creative Commons Attribution 3.0 Unported License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
AMC Mecanocaucho;Bosco Italia Spa;Ecophon Saint-Gobain;et al.;Head Acoustics;Mason Industries, Inc.
10th Convention of the European Acoustics Association, EAA 2023 -- 11 September 2023 through 15 September 2023 -- -- 198863
Keywords: Acoustic Education; International Year Of Sound; Iys 2020; Public Awareness; Acoustic Noise; Social Aspects; Acoustic Education; International Year Of Sound; Iys 2020; Noise Annoyance; Opinion Surveys; Public Awareness; Public Engagement; Public Opinions; Turkishs; Widening Participation; Noise Pollution